A scale development study of CSR: hotel employees' perceptions. Issue 4 (26th February 2019) - Ko, Annie; Chan, Andrew; Wong, Simon C.K.
Abstract : Purpose: This study aimed to develop an industry-specific, original, valid and reliable scale for measuring hotel employees' perceptions of CSR activities undertaken by their organizations. Design/methodology/approach: Based on the solid grounding of a conceptual framework and a systematic scale development process, both qualitative and quantitative research approaches were used. Data were collected from 18 in-depth interviews with CSR/HR managers and employees working in world-renowned international hotel companies and local hotel groups in Hong Kong. A pilot study of 204 employee samples was subjected to exploratory factor analysis to determine the underlying factorial structure of the scale. A further 732 usable samples in the main survey were used to assess the latent structure and validity of the scale using confirmatory factor analysis. Findings: The scale revealed sound psychometric properties based on the findings from reliability and validity tests. The results of the analysis validated previous research that employees' perceptions of CSR are a multidimensional construct and the five-dimensional model for the hotel industry consists of employees, guests, local community, the natural environment and owners/investors. Practical implications: The developed scale can help organizational behavior researchers to examine the causal relationship between an organization's CSR activities and employees' outcomes, thereby enhancing further development of predictive and prescriptive studies that provide prescription to hotel managers with instrumental reason to pursue CSR in an organizational setting. Originality/value: This study is one of the first scale development studies of employees' perceptions in the context of the hotel industry.